Prevalence, outcomes and risk factors of acute kidney injury in surgical intensive care unit: A multi-center thai university-based surgical intensive care units study (THAI-SICU study) - Pisitsak C. (2017)
© 2016, Medical Association of Thailand. All rights reserved. Objective: Acute kidney injury (AKI) is one of the most common problems in critically ill patients. AKI associates with poor outcome in ICU. The recognition of the prevalence and risk factors of AKI is important. This could lead to the prevention of AKI and improve patient’s outcome. This study aims to identify the prevalence, outcomes and independent risk factors of AKI in Thai surgical intensive care units. Material and Method: We conducted the prospective cohort study from nine university-based SICUs. The patients were diagnosed AKI by Acute Kidney Injury Network (AKIN) classification. The types of RRT and outcomes including mortality were collected. The risk factors of AKI were identified. Results: A total cohort of 4,652 patients was included for the present study. AKI was diagnosed in 786 (16.89%) patients. The ICU mortality was higher in patients with AKI (29.90% vs. 5.48%, p-value < 0.001). Among patients with AKI staging, we found that those with AKIN III had higher ICU mortality compared to patients with AKIN II and AKIN I respectively (47.66% vs. 26.67% vs. 14.69%, p-value < 0.001). Patients with AKI had higher 28 day-mortality compared with those without AKI (37.53% vs. 8.98%, p-value < 0.001). The independent risk factors of AKI were higher APACHE II scores (OR 1.04, 95% CI 1.01-1.06, p-value = 0.001), lower serum albumin (OR 0.82, 95% CI 0.70-0.97, p-value = 0.020), organ failures which were in the gastrointestinal system (OR 1.53, 95% CI 1.13-2.08, p-value = 0.007), cardiovascular system (OR 1.95, 95% CI 1.34- 2.83, p-value < 0.001), neurological system (OR 1.37, 95% CI 1.02-1.85, p-value = 0.038) and urinary system (OR 7.00, 95% CI 5.21-9.40, p-value < 0.001). Conclusion: Acute kidney injury associates with poor outcomes including increased ICU and 28-day mortality. Independent risk factors of AKI in the present study were higher APACHE II scores, lower serum albumin and organ failures on admission.